2017
DOI: 10.3389/fnsyn.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

What the Spectrum of Microglial Functions Can Teach us About Fetal Alcohol Spectrum Disorder

Abstract: Alcohol exposure during gestation can lead to severe defects in brain development and lifelong physical, behavioral and learning deficits that are classified under the umbrella term fetal alcohol spectrum disorder (FASD). Sadly, FASD is diagnosed at an alarmingly high rate, affecting 2%-5% of live births in the United States, making it the most common non-heritable cause of mental disability. Currently, no standard therapies exist that are effective at battling FASD symptoms, highlighting a pressing need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 171 publications
(310 reference statements)
0
11
0
Order By: Relevance
“…We chose to focus on microglial functions after developmental EtOH exposure because of the many diverse and complex roles that these cells play, from being ‘immune sentinels’ that can detect and resolve insults in the diseased brain to also being ‘gardeners’ that can selectively prune synaptic connections and support neuronal health under physiological conditions (as reviewed by (Hughes, 2012; Rohan Walker and Yirmiya, 2016; Tremblay et al, 2011; Wong et al, 2017). Currently, a body of work suggests that microglial immune functions may be triggered by high binge levels of EtOH exposure.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to focus on microglial functions after developmental EtOH exposure because of the many diverse and complex roles that these cells play, from being ‘immune sentinels’ that can detect and resolve insults in the diseased brain to also being ‘gardeners’ that can selectively prune synaptic connections and support neuronal health under physiological conditions (as reviewed by (Hughes, 2012; Rohan Walker and Yirmiya, 2016; Tremblay et al, 2011; Wong et al, 2017). Currently, a body of work suggests that microglial immune functions may be triggered by high binge levels of EtOH exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Given the roles of microglia in synaptic circuit formation and rearrangement (Ikegami et al, 2019), disruption of these functions could directly cause neuropathology found in FASD. Previous research in the field has already demonstrated both direct and indirect negative effects of developmental alcohol on microglia (reviewed in (Wong et al, 2017)). Our findings suggest that microglia may be sensitive to as little as one dose of EtOH in early development, which supports other studies showing similarly fast microglial responses to EtOH (Ahlers et al, 2015).…”
Section: Alcohol Exposure and Microgliamentioning
confidence: 99%
“…The effects of early exposure to ethanol exposure on microglia Neuroimmune changes have been reported after both adult and developmental EtOH exposure. Microglia are critical for neuronal development and are highly reactive to disturbances in the brain milieu making them likely targets for EtOH exposure (Wong et al, 2017). In fact, changes in microglia have been reported throughout the brain in animal models of developmental EtOH exposure, including exposure limited to the BGS (Kane &Drew, 2020).…”
Section: 3mentioning
confidence: 99%